Mapping displacement through lived experiences: Countermapping transit-induced gentrification in Kitchener-Waterloo, Ontario - Brian Doucet (Radical Housing Journal, 2022)
This article seeks to enhance our understanding of the role transit infrastructure plays in shaping patterns of gentrification and displacement by directly engaging with residents living along a new light rail transit (LRT) line who are affected by these processes. Displacement is difficult, if not impossible to statistically measure, yet much of the literature on transit-induced gentrification relies on quantitative analysis. Our approach is based on a collaboration between academic and non-academic partners that assembles, analyses and amplifies the experiences of marginalised residents in order to shift planning, policy and political conversations about the nature of change within our region. Through interviews with approximately fifty low-income residents living along a new LRT corridor in Waterloo Region, we analyse patterns, processes and experiences of displacement and the loss of already existing affordable housing. This information has been mapped to produce narratives that counter the dominant views which have celebrated an urban revival along the LRT corridor. Our research emphasises the need to incorporate lived experiences of displacement into central positions within the debates that make and shape cities.